1990
DOI: 10.1093/schbul/16.2.263
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in Identifying Subtypes of Schizophrenia: A Latent Class Analytic Approach

Abstract: Past literature suggests that schizophrenic men and women may be at different risks for developing different subtypes of schizophrenia. This hypothesis was tested using data from the well-known retrospective cohort family studies, the Iowa 500 and the Iowa non-500. The sample consisted of 171 male and 161 female DSM-III schizophrenic patients and 713 of their first-degree relatives. First, bivariate tests for gender differences were conducted regarding family morbidity, age of onset, premorbid history, season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
2
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(78 citation statements)
references
References 44 publications
10
64
2
2
Order By: Relevance
“…Since the classic work of Lorr et al (39), many attempts have been made, by using a range of statistical methods, to define objective subtypes of schizophrenia (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). In subjects from the Irish Study of High-Density Schizophrenia Families who met DSM-III-R criteria for schizophrenia, we found evidence, by using latent class analysis applied to the 11 items from the Major Symptoms of Schizophrenia Scale plus age at onset and gender, for at least five distinct syndromes.…”
Section: Latent Class Analysismentioning
confidence: 99%
“…Since the classic work of Lorr et al (39), many attempts have been made, by using a range of statistical methods, to define objective subtypes of schizophrenia (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). In subjects from the Irish Study of High-Density Schizophrenia Families who met DSM-III-R criteria for schizophrenia, we found evidence, by using latent class analysis applied to the 11 items from the Major Symptoms of Schizophrenia Scale plus age at onset and gender, for at least five distinct syndromes.…”
Section: Latent Class Analysismentioning
confidence: 99%
“…Relative to female patients, male subjects are more likely to present an earlier onset of the disorder, 1,2 more severe negative symptoms, [3][4][5][6] a greater number of hospitalizations, 7 poorer occupational and social outcome, 8 and poorer premorbid functioning. [9][10][11] Also, several neuroimaging studies have shown that male subjects with schizophrenia present more structural brain abnormalities than females. [12][13][14][15][16] Such clinical and neurobiological findings, added to the evidence that there are gender-related neurodevelopmental variations in the human brain, [17][18] have been taken as indicative of an etiological heterogeneity for schizophrenia, with males being more prone to a more neurodevelopmental form of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Such clinical and neurobiological findings, added to the evidence that there are gender-related neurodevelopmental variations in the human brain, [17][18] have been taken as indicative of an etiological heterogeneity for schizophrenia, with males being more prone to a more neurodevelopmental form of the disorder. 10,[19][20][21] One area of particular interest to neurodevelopmental theories of schizophrenia concerns the investigation of children and adolescents with first-degree relatives affected by the disorder. 22 Several studies have shown that such children and adolescents at risk for schizophrenia have a greater degree of cognitive, social and motor development problems when compared to not-at-risk subjects of the same age range.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to positive psychotic symptoms, a large number of studies have reached the conclusion that both men and women experience the same level of positive symptoms 23,46 , although certain symptoms such as auditory hallucinations and persecutory delusions are more frequent in women 44 . The analysis regarding prodromic symptoms in our sample comes to similar conclusions, with women showing an early onset of the disease presenting a higher frequency of subclinical senso-perceptive disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies have shown that women manifest more affective symptoms, atypical and cyclical forms of psychosis as well as a higher incidence in the diagnosis of paranoid and disorganized subtypes 4,44,45 . Szymanski et al 45 observed less illogical thinking but more anxiety, inappropriate affect and bizarre behaviour in women than men with first psychotic episode.…”
Section: Clinical Variablesmentioning
confidence: 93%